CCL22 signaling contributes to sorafenib resistance in hepatitis B virus-associated hepatocellular carcinoma. (July 2020) - Gao, Yanan; Fan, Xing; Li, Nan; Du, Chengzhi; Yang, Bin; Qin, Wenhao; Fu, Jing; Markowitz, Geoffrey J.; Wang, Hongyang; Ma, Jianli; Cheng, Shuqun; Yang, Pengyuan
Graphical abstract: Highlights: Lymphocytes-mediated immunity was involved in sorafenib resistance. Sorafenib upregulated CCL22 and CCL17 via TNF-α-RIP1-NF-κB signaling pathway. Combination therapy enhanced the antitumor efficacy to overcome drug resistance. Blocking CCL22 signaling could be a potential therapeutic strategy for HBV-associated HCC. Abstract: The HBV-initiated hepatocellular carcinoma (HCC) frequently develops from or accompanies long-term chronic hepatitis, inflammation, and cirrhosis, and has a poor prognosis. Sorafenib, an orally active multi-kinase inhibitor, currently the most common approved drug for first-line systemic treatment of advanced HCC, only improves overall survival of three months, suggesting the need for new therapeutic strategies. In this study, we identified that sorafenib selectively resisted in immune competent C57BL/6 mice but not nude mice. The chemokines CCL22 and CCL17 were upregulated by sorafenib, which elevated dramatically higher in HBV-associated HCC. Mechanically, sorafenib accelerates CCL22 expression via TNF-α-RIP1-NF-κB signaling pathway. Blocking CCL22 signaling with antagonist C-021 and sorafenib treated in combination can inhibit tumor growth and enhance the antitumor response, whereas no significant differences in tumor burden were observed in nude mice upon addition of C-021. These findings strongly suggest that CCL22 signaling pathway strongly contributes to sorafenib resistance in HBV-associated HCC, indicating a potential therapeutic strategy for immunological chemotherapy complementing first-line agents against HBV-associated HCC.